The effects of active recovery and carbohydrate intake on HRV during 48 hours in athletes after a vigorous-intensity physical activity - Aras, D.; Karakoc, B.; Koz, M.; Bizati, O. (Science & Sports, 2017)
Objectives: The purpose of this study was to investigate the effects of active recovery and CHO intake after a vigorous-intensity physical activity during 48 hours by using heart rate variability (HRV) measurements in athletes.